2017
DOI: 10.1371/journal.pone.0176696
|View full text |Cite|
|
Sign up to set email alerts
|

Bacterial community and arsenic functional genes diversity in arsenic contaminated soils from different geographic locations

Abstract: To understand how soil microbial communities and arsenic (As) functional genes respond to soil arsenic (As) contamination, five soils contaminated with As at different levels were collected from diverse geographic locations, incubated for 54 days under flooded conditions, and examined by both MiSeq sequencing of 16S rRNA gene amplicons and functional gene microarray (GeoChip 4.0). The results showed that both bacterial community structure and As functional gene structure differed among geographical locations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 63 publications
(78 reference statements)
6
23
1
Order By: Relevance
“…As it is for Betaproteobacteria class, Gammaproteobacteria did not show a significant difference between the xanthates doses and their mixed-chemicals doses. The proportion of Proteobacteria in Ni-treated samples (15%) was lower than that recently observed in arsenic-contaminated soil where it was the dominant phylum (29-38% abundant), Alphaproteobacteria and Gammaproteobacteria being the most and least abundant classes [55]. The most abundant and proportionally different bacterial classes between the xanthate-treated samples and their corresponding mixtures-treated samples were presented, both in the case of 50 µg·g −1 soil ( Figure 5A) and in the case of 100 µg·g −1 soil ( Figure 5B).…”
Section: Taxonomic Compositioncontrasting
confidence: 66%
“…As it is for Betaproteobacteria class, Gammaproteobacteria did not show a significant difference between the xanthates doses and their mixed-chemicals doses. The proportion of Proteobacteria in Ni-treated samples (15%) was lower than that recently observed in arsenic-contaminated soil where it was the dominant phylum (29-38% abundant), Alphaproteobacteria and Gammaproteobacteria being the most and least abundant classes [55]. The most abundant and proportionally different bacterial classes between the xanthate-treated samples and their corresponding mixtures-treated samples were presented, both in the case of 50 µg·g −1 soil ( Figure 5A) and in the case of 100 µg·g −1 soil ( Figure 5B).…”
Section: Taxonomic Compositioncontrasting
confidence: 66%
“…Similar observations were reported by Hassan et al where abundance of Betaproteobacteria was observed as the most abundant class (~69% of the community) in a comparative examination of microbial communities from 24 groundwater samples in Bangladesh [17]. In addition to BDP aquifers, this bacterial class also has been shown to dominate the microbial communities in As-contaminated soils from China and the United Kingdom [18]. Taken together, these observations are indicative of an emerging pattern where members of Betaproteobacteria are major inhabitants of arsenic-contaminated subsurface in geographically distant regions.…”
Section: Introductionsupporting
confidence: 86%
“…Relative importance analysis showed that Chloroflexi was strongly influenced by Sbrec, Astot, and Asrec, while Proteobacteria was mainly influenced by Astot. According to previous reports, Anaerolineaceae, as a specific anaerobic of Chloroflexi, existed in various environmental media contaminated by Sb and As [57,58], and Anaerolineaceae has also been reported to be widely distributed in contaminated paddy soil in China, Britain, and Bangladesh [59]. We found that Anaerolineaceae was the most abundant family of Chloroflexi and it decreased with the deepening of soil layer.…”
Section: Effects Of Sb and As Contamination Fractions On Bacterial Cosupporting
confidence: 51%